Kelayakan Bukti Modern Dalam Pembuktian Tindak Pidana Korupsi Indonesia Studi Atas Kasus Representatif 2020–2025 - Ferdian Rinaldi; Anry Firmansyah (Law Department Jenderal Achmad Yani University, 2026)
This article analyzes the admissibility and evidentiary worthiness of modern evidence in proving corruption offenses in Indonesia. The development of corruption cases shows that criminal proof no longer relies solely on witnesses and conventional documents, but also on electronic documents, transaction data, state loss audits, expert testimony, digital records, and a series of inferences connecting evidence to the elements of the offense. The main issues examined in this article are the legal patterns surrounding the use of modern evidence in representative corruption cases from 2020 to 2025 and how the worthiness of such evidence can be analyzed through the traceability of process, integrity of evidence, validity of examination methods, rationality of the relationship between evidence and the elements of the offense, and protection of the defendant’s rights. This research uses a normative legal method with statutory, conceptual, and case approaches. The research materials were obtained through document study of legislation, ICW reports, KPK reports, documents from relevant organizations, and literature on the law of evidence. The findings show that formal recognition of electronic evidence is insufficient to guarantee the evidentiary worthiness of evidence in corruption cases. Modern evidence must be examined in terms of process, integrity, method, logical connection with the elements of the offense, and the openness of such evidence to be challenged by the defendant.